Stability analysis of stage open stope with delayed backfill:modelling and experimental studies - Wu Di; Deng Tengfei; Sun Guanghua (矿业科学学报, 2018)
In terms of the stability of backfill and surrounding rock during the mining process of Stage open stoping with delayed backfill at Longwan Iron Mine，a similar simulation experiment was conducted to investigate the displacement field evolution of the stope and its surrounding rocks during the mining and filling processes.The backfilling stope was simplified into mechanical model of thin plate，which was imported into the platform of software COMSOL Multiphysics to carry out numerical analysis.The numerical computation results were compared with the similar simulation outcomes，and it was noticed that they agreed well with each other.This indicated that the evolution of displacement and strain obtained by numerical calculation accorded with the actual conditions basically.The results showed that the stope stability was closely related to the strength of ore body and backfill as well as the stope integrity.The displacement and strain field evolutions of the filling stope and its surrounding rocks obtained in this study can provide reference and data supporting for the mining and backfilling operations of similar mines.